2015
DOI: 10.12669/pjms.316.8338
|View full text |Cite
|
Sign up to set email alerts
|

Four-year follow-up of corneal aberrations and visual functionsof myopic patients after laser in situ keratomileusis

Abstract: Objective:To report on 4-year follow-up of corneal higher-order aberrations and daily visual functions of myopic patients after laser in situ keratomileusis (LASIK).Methods:One hundred thirty four eyes of 67 patients who underwent LASIK guided by aspherical ablation were included in this study. The vision, corneal spherical aberration (SphA) and Coma were recorded before LASIK and at 6 month and 4 year after LASIK. The evaluation of the questionnaire about daily visual functions was performed by the same physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…This technique has been reported to induce high-order aberrations. [24] Furthermore, the pupil offset from the visual axis can also induce high-order aberrations. Additional causes of high-order aberrations reported by other authors include wound response of the cornea after FS-LASIK, change in corneal shape after ablation, and individual differences in corneal biomechanical response.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been reported to induce high-order aberrations. [24] Furthermore, the pupil offset from the visual axis can also induce high-order aberrations. Additional causes of high-order aberrations reported by other authors include wound response of the cornea after FS-LASIK, change in corneal shape after ablation, and individual differences in corneal biomechanical response.…”
Section: Discussionmentioning
confidence: 99%
“…In der 4-Jahres-Studie nach LASIK von Liu et al [16] (n = 134; SÄ − 5,10 dpt) verlor kein Auge 1 Zeile oder mehr. Dieses Ergebnis liegt deutlich über dem der vorliegenden Studie mit 20 % 1-Zeilen-Verlust.…”
Section: Diskussionunclassified
“…Darüber hinaus scheinen die Lasersettings eine extrem wichtige Rolle für die Visusergebnisse nicht nur kurzfristig, sondern auch mittelfristig zu spielen. Die außerordentliche Stabilität des ReLEx-SMILE-Verfahrens im Vergleich zu LASIK [16] ließ sich auch in dieser Studie bestätigen.…”
Section: Diskussionunclassified
“…Some reports have suggested that coma and spherical aberrations play a major role in affecting vision quality and showed a correlation between starburst and spherical aberrations, glare and spherical aberrations, with as well as a correlation between diplopia and horizontal coma (17,18). Coma can be caused by the corneal flap, an unsmooth corneal stromal bed, as well as the corneal wound-healing response (19)(20)(21). Previous studies have suggested that postoperative spherical aberrations may be caused by the "cosine effect", and that ablation changes the corneal shape from long oval to flat oval after surgery (22).…”
Section: Discussionmentioning
confidence: 99%